Developing a Python program for collecting stock data from webpages in English - Budiman, Alvin Putera (Nanyang Technological University, 2024)
This project aims to develop a Python program capable of efficiently collecting stock data from various webpages in English. The program utilizes web scraping techniques to extract essential information from stock websites, focusing primarily on retrieving current stock values and key metrics necessary for conducting discounted cash flow (DCF) analysis. The project involves several key components such as web scraping module, data extraction, DCF calculation, undervalued stock identification, and User Interface. Overall, this project aims to provide a valuable tool for investors seeking to analyse stock data and identify undervalued stocks in the market. By automating the data collection process and leveraging advanced analysis techniques, the Python program offers a systematic approach to stock valuation and investment decision-making.